x+y+x+y+2x+2z=

Simple and best practice solution for x+y+x+y+2x+2z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+y+x+y+2x+2z= equation:


Simplifying
x + y + x + y + 2x + 2z = 0

Reorder the terms:
x + x + 2x + y + y + 2z = 0

Combine like terms: x + x = 2x
2x + 2x + y + y + 2z = 0

Combine like terms: 2x + 2x = 4x
4x + y + y + 2z = 0

Combine like terms: y + y = 2y
4x + 2y + 2z = 0

Solving
4x + 2y + 2z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2y' to each side of the equation.
4x + 2y + -2y + 2z = 0 + -2y

Combine like terms: 2y + -2y = 0
4x + 0 + 2z = 0 + -2y
4x + 2z = 0 + -2y
Remove the zero:
4x + 2z = -2y

Add '-2z' to each side of the equation.
4x + 2z + -2z = -2y + -2z

Combine like terms: 2z + -2z = 0
4x + 0 = -2y + -2z
4x = -2y + -2z

Divide each side by '4'.
x = -0.5y + -0.5z

Simplifying
x = -0.5y + -0.5z

See similar equations:

| 7x+2.0=-4x-5.3 | | 6(4x-9)-7=6(x-3)+65 | | 2x^2+24-60=0 | | 15x+20=20x-5 | | 6(4x-9)-7=6(x-3) | | x^2+6x+-55=0 | | .5(2x-2)=5x+4 | | f(x)=(x+6)-49 | | 48y^2-13y=0 | | -29=5(2a-1)+3 | | 4(x+2)=8(x-1)-12 | | 2n^2+11n-90=0 | | 7.512=4.2/x | | 9y^2-18=0 | | 4(2+3c)=96 | | -4(1-3b)=21+7b | | 11x-(3x-8)=64 | | 2(4z+4)-9=55 | | 4K+2=5.5 | | -6x=7+5x+5x | | 0x-6y=30 | | h(x)=(x+4)(x-6)(x-8) | | 7z+1/9=8z+2/9 | | 2/3n=46 | | 2x-7x+67=3x+35 | | y/6= | | -3+2(8b-5)=7-31 | | (h+3)(h)-54=0 | | 5x+4/9=6x+7/9 | | -2/5x-8=20+3/4x | | 10=m+8 | | (3x+1)(8x-3)=0 |

Equations solver categories